Pemberdayaan Masyarakat HIPPAM Tirta Bahari dengan Sanitasi yang Baik untuk Hidup yang Laik - Setyaningrum, Dyah; Elvania, Nindy Callista; Mushthofa, Mushthofa (Universitas Nusantara PGRI Kediri, 2025)
Clean water sanitation is an effort to maintain cleanliness and prevent the transmission of waterborne diseases to achieve community welfare in an area. This community service aims to increase the knowledge of the managers and consumers of HIPPAM Tirta Bahari Banjarjo Village, Bancar Subdistrict, Tuban Regency in managing clean water to fulfill basic proper sanitation. There are two activities to achieve this goal, the first activity was carried out on 19 August 2024 and related to the socialization of basic sanitation for a decent life. The second activity was carried out on 16 September 2024 related to making filtration with natural filters. Evaluation of the success of the socialization of this activity was carried out through pre-test and post-test. The pre-test and post-test results showed that the participants' understanding had increased to 95%, meaning that the participants could receive the material well. However, there is still a need for long-term evaluation regarding the sustainability of the program. Cooperation from all parties in implementing clean living is the most important factor, so that the effectiveness of basic sanitation can be fulfilled.